Utility of mangled extremity severity score in severely injured lower limbs - Bhatta, Toya Raj; Gyawali, B; Tamrakar, R; Acharya, BK; Shrestha, SK; Pradhan, NMS; Giri, SK (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Massive lower extremity trauma,in particular open tibial fractures with associated vascular injuries, present an immediate and complex decision-making challenge between a limb salvage attempt and primary amputation. Medical and surgical advances of the past two decades have improved the ability to reconstruct severely injured limb. Limbs that once would have been amputated are now routinely managed with complex reconstruction protocol. Mangled extremity severity score is one of the scoring systems to predict the fate of limbs after severe limb injuries. Methods: Patients fulfilling the inclusion criteria were evaluated with MESS, at the same time treatment protocol for management of injuries of lower limb were followed independently by attending orthopedic surgeon. Mean MESS for salvaged and amputated limbs were calculated and its reliability for prediction of fate of injured limb was assessed using software SPSS v16. Result: The age of patient ranges from 10 to 65 yrs with mean age 35.83. The most common mechanism of injury was Road Traffic Accident followed by fall from height. The mean MESS score for salvaged limbs was 4.18 and for amputated limbs was 8.12 suggesting significant difference in mean scores. The sensitivity (the probability that limbs requiring amputation will have MESS at or above 7) was found to be 75%. The specificity of MESS (the probability that salvage limbs will have MESS < 7) was 95.45%. Conclusion: MESS is a reliable indicator in decision making process whether a limb can be salvaged or needs amputation. The mangled lower extremity with the score of less than 7 may be salvaged and 7 or more may need amputation. JSSN 2015; 18 (1), Page: 23-25